USE OF SUGAR-FREE CHEWING GUM (XYLITOL) TO ACCELERATE GASTROINTESTINAL MOTILITY RECOVERY IN POST-APPENDECTOMY PATIENTS AT KANJURUHAN HOSPITAL - Hadis, Roidah (Indonesian Journal Of Empirical Nursing Sciences, 2026)
Introduction: Appendectomy may cause delayed gastrointestinal motility recovery, increasing the risk of postoperative complications, prolonging hospital stay, causing patient discomfort, and delaying oral feeding, particularly in patients who undergo preoperative fasting. This study aimed to describe the use of sugar-free chewing gum containing xylitol as a non-pharmacological nursing intervention to accelerate gastrointestinal motility recovery in post-appendectomy patients at Kanjuruhan Regional General Hospital. Methods: A case study design was conducted involving two post-appendectomy patients presenting with hypoactive bowel sounds averaging 1–2 times per minute, mild abdominal distension, and absence of flatus. The intervention was initiated two hours after surgery by administering xylitol chewing gum three times daily at six-hour intervals, with each session lasting ten minutes using four pieces of chewing gum. Gastrointestinal motility was assessed through bowel sound frequency and the occurrence of flatus before and after the intervention. Results: The findings showed a gradual increase in bowel sound frequency from hypoactive levels to increased activity, accompanied by the appearance of flatus within six hours after the intervention. Conclusion: Sugar-free chewing gum therapy may accelerate gastrointestinal motility recovery and support earlier oral intake, making it a simple, safe, and effective complementary nursing intervention for post-appendectomy patients.